Productivity in New Zealand 1988 to 2002 - Melleny Black; Melody Guy; Nathan McLellan (New Zealand Government, The Treasury, 2003)
This paper reports new aggregate and industry productivity series for the New Zealand economy for the period 1988 to 2002. These productivity series are intended for ongoing monitoring of New Zealand's productivity performance and for use in further analyses investigating the evolution, sources and determinants of New Zealand's productivity growth. Productivity series are constructed using index number techniques and industry data sourced from Statistics New Zealand. Throughout, comparisons are made with the productivity estimates reported in Diewert and Lawrence's (1999), Measuring New Zealand's Productivity. Industry data are also used to construct productivity series that are comparable with the market sector productivity series published by the Australian Bureau of Statistics. The comparison between Australia and New Zealand shows that market sector multifactor productivity has been similar in both countries over the full sample period. Since 1994 average labour productivity growth has been higher in Australia, which reflects the relatively lower rate of physical capital accumulation in New Zealand after 1993. On the other hand, New Zealand's capital productivity growth has been higher than Australia's capital productivity growth since 1994, reflecting the relatively higher growth in hours worked in New Zealand.
Keywords: C43; O47; 330; Economic growth; productivity measurement; index numbers; Australia and New Zealand comparison